3-D Turbulent Unsteady Heat Transfer in a Rectangular Duct with Arrays - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2009)
In order to simulate heat producing elements on electronic circuits, heat input at the inlet of a rectangular duct is supposed to vary sinusoidally and transient forced convection for turbulent flows are investigated numerically. This study focuses on a 3-D numerical analysis Of unsteady forced convection in hydrodynamically developed and thermally developing turbulent air flow in rectangular duct, subjected to periodic variation of the inlet temperature. The experimental and numerical studies were conducted on the range of Reynolds numbers of 11242, 17673 and 22284 for turbulent flow and inlet frequencies (beta) of 0.16 and 0.24 Hz of the periodic heat input. Numerical results were obtained for the fully developed parabolic velocity profile under the developing temperature profile for the fifth kind boundary condition which was verified by computational fluid dynamics (CFD) code called STAR CCM+. Temperature variations along the centerline of the rectangular duct were observed to be thermal oscillations with the same frequency as the inlet periodic heat input and amplitudes that decayed exponentially with distance along the duct.
Keywords: Heat transfer; three dimensional; unsteady; CFD; amplitude; turbulent flow; LAMINAR FORCED-CONVECTION; INLET TEMPERATURE; PERIODIC VARIATION; FLOW; CHANNELS; WALLS